Greece under SYRIZA government and the European Union - Ratajczak, Anna (Wydział Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2018)
In the paper, the author analyses three years of the rule of the left-wing SYRIZA in Greece. She discusses the basis of the party’s historical victory in the parliamentary elections in 2015. In addition, she analyses the course of negotiations with Greek creditors regarding the third economic adjustment programme for Greece. She also points out the necessity of gradual resignation from anti-austerity agenda and social reactions against introduced reforms. In the final part, the author of the paper outlines the current challenges of the Greek government.

Autorka w artykule poddaje analizie trzy lata rządów lewicowej SYRIZY w Grecji. Omawia podłoże historycznego zwycięstwa partii pod wodzą Aleksisa Tsiprasa w wyborach parlamentarnych w 2015 r. Ponadto analizuje przebieg negocjacji z greckimi wierzycielami dotyczącymi III programu pomocowego. Zwraca też uwagę na konieczność stopniowego odchodzenia od sprzeciwu wobec polityki oszczędności oraz reakcje społeczne na wprowadzane reformy. W końcowej części, autorka pracy wskazuje na bieżące wyzwania rządu greckiego.
Grecja pod rządami SYRIZY a Unia Europejska
Keywords: Greece; SYRIZA; Alexis Tsipras; financial crisis; Grecja; SYRIZA; Aleksis Tsipras; kryzys finansowy